Higher Education Quality Assurance System - Meisuri, Meisuri; Harjati, Purwiro; Pahrudin, Agus (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
The aim of the research is to describe the quality assurance system in higher education. The type of research is qualitative research with literature study. Data collection is done by searching for sources and constructing them from various sources such as books, journals and research that has already been carried out. Meanwhile, in analyzing the data, data triangulation, member checking and auditing techniques were used, as well as data analysis techniques according to Miles & Huberman, namely data reduction, data display and conclusions. The research findings are that educational institutions need to carry out quality assurance processes both internally and externally. Responsibility for the quality of higher education is completely handed over to the university concerned. To become an effective higher education institution, it can utilize all the resources it has, such as lecturers as teaching staff and educational staff who are elements of higher education human resources; in addition to material resources, machines including facilities and energy, money, and information including data owned by universities. Efforts to develop the quality of HEIs are carried out by increasing student capacity directed towards relevant fields, increasing link and match in terms of abilities and skills, as well as improving the quality of lecturers. Monitoring and evaluation must be carried out as well as the stages of determination, implementation, evaluation, control and improvement (PPEPP) in implementing quality assurance, so that it does not deviate from the goals that have been set and can provide the best results for parents, students, and most importantly the world market. work both domestically and abroad.